The perspectives of NETosis on the progression of obesity and obesity-related diseases: mechanisms and applications - Li, Jinyu; Yin, Lijia; Chen, Siyi; Li, Zelin; Ding, Jiatong; Wu, Jiaqiang; Yang, Kangping; Xu, Jixiong (Frontiers in Cell and Developmental Biology, 2023)
Obesity is a disease commonly associated with urbanization and can also be characterized as a systemic, chronic metabolic condition resulting from an imbalance between energy intake and expenditure. The World Health Organization (WHO) has identified obesity as the most serious chronic disease that is increasingly prevalent in the world population. If left untreated, it can lead to dangerous health issues such as hypertension, hyperglycemia, hyperlipidemia, hyperuricemia, nonalcoholic steatohepatitis, atherosclerosis, and vulnerability to cardiovascular and cerebrovascular events. The specific mechanisms by which obesity affects the development of these diseases can be refined to the effect on immune cells. Existing studies have shown that the development of obesity and its associated diseases is closely related to the balance or lack thereof in the number and function of various immune cells, of which neutrophils are the most abundant immune cells in humans, infiltrating and accumulating in the adipose tissues of obese individuals, whereas NETosis, as a newly discovered type of neutrophil-related cell death, its role in the development of obesity and related diseases is increasingly emphasized. The article reviews the significant role that NETosis plays in the development of obesity and related diseases, such as diabetes and its complications. It discusses the epidemiology and negative impacts of obesity, explains the mechanisms of NETosis, and examines its potential as a targeted drug to treat obesity and associated ailments.